Association of the CKM rs8111989 polymorphism with injury epidemiology in football players - Varillas-Delgado, D.; Morencos, E.; Gutierrez-Hellín, J.; Aguilar-Navarro, M.; Maestro, A.; Perucho, T.; Del Coso, J. (International Journal of Sports Medicine, 2023)
The influence of the rs8111989 polymorphism in the muscle-specific creatine kinase gene (CKM) on injury incidence is unknown. The aim was to investigate CKM polymorphism on injury incidence in high-performance football players. A cohort of 109 high-performance players was genotyped by using saliva samples. Injury incidence was similar in players with the GG, GA, and AA genotypes and did not modify incidence during training or match exposure (p=0.583 and p=0.737 respectively). GG players had a higher frequency of slight-severity injuries (60.0 vs. 10.2 vs. 24.2%, p<0.001), while GA players had a higher frequency of severe injuries (16.7 vs. 30.8 vs. 10.0%, p=0.021). GA players also had a higher frequency of muscle tears (34.8 vs. 59.0 vs. 20.0%, p<0.001). Muscle contracture was a more frequent injury in players with the GG genotype (40.0%, p<0.001). G allele carriers had lower frequencies of gradual-onset injuries (4.1 vs. 16.7%, p=0.035) and recurrent injuries (6.1 vs. 16.7%, p=0.003) than AA players. A allele carriers had higher frequency of severe injuries (10.0 vs. 21.9%, p=0.044) than GG players. Genotypes in the CKM rs8111989 polymorphism did not affect injury incidence in high-performance football players. Players with the GA genotype were more prone to severe injuries and muscle tears when compared to GG and AA players.